CREATING A SPACE FOR STORIES AND STORYTELLING IN MATHEMATICS CLASSROOM: A PEDAGOGICAL ENQUIRY - Kumar Chandoria, Virend; Singh, Pooja; Vajpai, Shikha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Storytelling has been a tool for teaching and learning across various disciplines, but rarely seen in mathematics. This research explores the effectiveness of storytelling as a pedagogical tool in mathematics education. The objective of the study is to try out the effect of storytelling as a pedagogical approach in mathematics learning at primary level and to study the effectiveness of storytelling in learning mathematics. To investigate this, the qualitative and descriptive methodologies have been used in this research. The self-made stories along with specific themes have been used as a tool to implement this with students of the schools, which have been selected by random sampling method. Effectiveness of the storytelling was evaluated through classroom observation that has been recorded in the form of verbatims by the students of the class during the storytelling session. The analysis based upon the eight themes and the literature reviews in this research supports the project’s approach by highlighting the effectiveness of storytelling as a pedagogical approach in mathematics which enhances conceptual understanding, engagement, communication, reasoning, problem-solving skills, connection with real-life experiences, collaborative learning, motivation, and retention of concepts, which leads to the findings for the research. The findings reveals that storytelling can be an effective pedagogical tool in mathematics education, enhancing conceptual understanding , engagement among students and with the Teacher, communicating mathematically, reasoning and problem solving skills, connecting with Real-Life Experiences, collaborative learning, motivation, retention and many more compared to those taught through traditional methods. The study highlights the need for research on a larger scale, exploring the long term effects and potential implementation of storytelling in various educational contexts. The storytelling into mathematics curriculum can make the class more enjoyable, interactive by providing a good learning environment. Ultimately, the Research work has proven to be highly effective by improving the overall education outcomes.